Influence of the Frontside Charge Inversion Layer on the Minority Carrier Collection in Backside Contacted Liquid Phase Crystallized Silicon on Glass Solar Cells. Issue 9 (21st July 2017) - Frijnts, Tim; Preissler, Natalie; Gall, Stefan; Neubert, Sebastian; Rech, Bernd; Schlatmann, Rutger
Abstract : External quantum efficiency and light beam induced current measurements were used to investigate backside contacted solar cells made on p‐type, liquid phase crystallized silicon on glass (LPC‐Si). Among other differences, these cells had either a SiO x N y or an Al2 O3 /SiO2 based frontside surface passivation (interlayer). From the measurements it was observed that the cell with the SiO x N y interlayer showed a charge carrier collection from below the absorber contact and from outside the cell area that is much larger than expected from the typical diffusion length in LPC‐Si. This was in contrast to the cell with the Al2 O3 /SiO2 interlayer, which showed the expected behavior. It was also observed that for the cell with the SiO x N y interlayer, both the collection outside and the collection inside the cell area were strongly bias light dependent. It is argued that these charge carriers collected from outside the cell area are collected through a frontside charge inversion layer. This was supported by an analysis of the measured wavelength and bias light dependence of the collection outside the cell area for the cell with the SiO x N y interlayer. The measured fixed charge density of the interlayer stack with the SiO x N y layer was used to estimate the sheet resistance of the frontside charge inversion layer and this sheet resistance could explain the bias light dependence of the collection outside the cell area. The fixed charge density was also used to simulate the excess carrier density dependence of effective surface recombination at the SiO x N y /c‐Si interface and these simulation results could explain the bias light dependence of the collection inside the cell area. Abstract : Backside contacted solar cells made on p type, liquid phase crystallized silicon (LPC‐Si) with SiO x N y or Al2 O3 /SiO2 based frontside passivation are investigated with EQE and light beam induced current (LBIC) measurements. The large collection below the absorber contact and outside the cell area, obtained only for the cell with SiO x N y layer, is attributed to collection through a frontside inversion layer.